2012
DOI: 10.1097/scs.0b013e31825653fa
|View full text |Cite
|
Sign up to set email alerts
|

Does Helmet Therapy Influence the Ear Shift in Positional Plagiocephaly?

Abstract: Helmet treatment significantly improves an initial malposition of the external ear in infants with positional plagiocephaly. A severe ear shift can be associated with a moderate CVAI and vice versa. In contrast to the CVAI, small changes of the ear shift cannot be evaluated reliably by clinical investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 4 publications
2
17
0
Order By: Relevance
“…Cephalic index (CI) is head width (side to side) divided by head length (front to back) multiplied by 100 [31]. Cranial vault asymmetry (CVA), the difference between diagonal measurements over the cranial vault or top of the head, was also used to assess head shape [32]. This was achieved by measuring from the frontozygomaticus (fz) (superolateral orbital rim) to a point that is approximately 30°from the opisthocranion (op) on the opposite side (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Cephalic index (CI) is head width (side to side) divided by head length (front to back) multiplied by 100 [31]. Cranial vault asymmetry (CVA), the difference between diagonal measurements over the cranial vault or top of the head, was also used to assess head shape [32]. This was achieved by measuring from the frontozygomaticus (fz) (superolateral orbital rim) to a point that is approximately 30°from the opisthocranion (op) on the opposite side (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Kluba et al [24] reported the effects of helmet therapy on pre-existing ear shift in patients with DP, implying that helmet therapy has a corrective effect. However, the same study showed that ear shift can arise de novo during helmet therapy in patients who did not have ear shift at the beginning of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…43 Of the 21 primary research articles, there were 7 Class II studies, 10,11,13,17,25,31,36 1 Class III study, 33 and 13 Class IV studies. 5,6,9,12,[14][15][16]20,26,35,37,39,41 …”
Section: Resultsmentioning
confidence: 99%
“…Six articles were excluded because they were not directly related to cranial orthoses therapy in deformational plagiocephaly (n = 5), or involved nonhuman subjects (n = 1). Of the remaining 36 papers, 21 were primary research literature articles, 5,6,[9][10][11][12][13][14][15][16][17]20,25,26,31,33,[35][36][37]39,41 12 were reviews, 7,8,[22][23][24]29,30,32,34,38,40,42 2 were letters, 3,18 and 1 described the methodology of an ongoing randomized controlled trial. 43 Of the 21 primary research articles, there were 7 Class II studies, 10,11,13,17,25,31,36 1 Class III study, 33 and 13 Class IV studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation